KAJIAN INTERDISIPLINER: KRIMINOLOGI DAN PENDIDIKAN KEWARGANEGARAAN DALAM MENCEGAH KEJAHATAN - Satrul, Hairul Saleh (Universitas Negeri Makassar, 2025)
Penelitian ini membahas keterkaitan antara Kriminologi dan Pendidikan Kewarganearaan dalam kerangka pencegahan kejahatan dan peningkatan kesadaran hukum di lingkungan pendidikan, khususnya sekolah. Pendekatan yang digunakan adalah studi kepustakaan dengan teknik analisi isi (content analysis) terhadap literatur ilmiah, peraturan perundang-undangan, laporan lembaga resmi seperti KPAI dan Kemendikbudristek, serta jurnal nasional dan internasional. Hasil kajian menunjukkan bahwa teori-teori kriminologi seperti Differential Association dan Social Control relevan untuk memahami dinamika perilaku menyimpang di lingkungan sekolah. Sementara itu, Pendidikan Kewarganegaraan memiliki peran strategi dalam membentuk identitas hukum siswa melalui proses internalisasi nilai, norma, dan tanggung jawab sosial. Integrasi kedua disiplin ini berpotensi melahirkan pendekatan preventif yang lebih efektif melalui kurikulum, pedagogi konstektual, serta kerja sama antar lembaga. Artikel ini merekomendasikan pengembangan model pembelajaran interdisipliner yang menggabungkan pendekatan hukum, sosial, dan moral dalam membentuk warga negara yang sadar hukum dan antikejahatan sejak usia sekolah.This study examines the relationship between Criminology and Civic Education within the framework of crime prevention and increasing legal awareness in educational settings, particularly schools. This study uses a library research approach with content analysis techniques applied to scientific literature, laws and regulations, reports from official institutions such as the Indonesian Child Protection Commission (KPAI) and the Ministry of Education, Culture, Research, and Technology, as well as national and international academic journals. The results of the study indicate that criminological theories such as Differential Association and Social Control are relevant to understanding the dynamics of deviant behavior in school environments, especially among students. These theories highlight the influence of peer relationships, weakening social ties, and structural pressures. Meanwhile, Civic Education plays a strategic role in shaping students' legal awareness and social responsibility through the internalization of values, norms, and civic character. However, the learning approach is often normative and detached from the sociological roots of delinquency. The integration of these two disciplines results in a more effective preventive approach through curriculum, contextual pedagogy, case-based discussions, and inter-institutional collaboration. This synergy enables education to function not only as a tool for norm transformation but also as a mechanism for critical understanding and social intervention. This article recommends the development of an interdisciplinary learning model that combines legal, social, and moral approaches to develop law-conscious and anti-crime citizens from school age, thus positioning schools as the basis for legal culture transformation.